Tradisi Maddoja Bine Dalam Peningkatan Kualitas Padi Terhadap Jual Beli Gabah Perpektif Fiqih Muamalah (Studi Kasus di Takkalasi Kabupaten Barru) - Rahmat Hidayat; Abd. Karim Faiz (SIGHAT: JURNAL HUKUM EKONOMI SYARIAH, 2024)
The Maddoja Bine tradition is a longstanding customary practice among the people of Takkalasi, Barru Regency. This tradition, observed by the community, aims to enhance both the production and quality of rice in the context of buying and selling paddy from the perspective of Fiqh Muamalah. Employing a qualitative, descriptive approach, this study conducts an in-depth exploration encompassing all aspects of the field research method, specifically field research. Data collection involves comprehensive interviews, observations, and documentation. The research findings conclude that the Maddoja Bine practice, conducted by the people of Takkalasi once a year during the arrival of the rainy season, is a deeply rooted tradition passed down through generations or from one's ancestors. Some members of the community believe that the Maddoja Bine tradition can increase crop yields and improve rice quality compared to when the tradition is not observed. From the perspective of Fiqh Muamalah, the practice of the Maddoja Bine tradition resulting in high-quality yields enables farmers to reap profits that can recover their investments, as the quality harvests can increase the price of paddy. To avoid transactions prohibited by religious teachings, both parties must adhere to the pillars, conditions, and ethics of trade.